KOSAKATA PADA KEMASAN DAN TEKNIK PENERJEMAHANNYA KE DALAM BAHASA ARAB - Regi Fajar Subhan (Arabic Literature Department, 2020)
This paper analyzes various techniques of translation which is used in the text on the package of several snack products that is produced in Indonesia. The most important thing to be known by consumer from the snack package is its expiration date and the composition of the product. This study discusses the translation techniques used from Indonesian into Arabic. Based on these problems, study aims to find out the techniques which is used by translator according to the theory of Molina and Albir (2002) which proposed 18 different techniques. The method for this research is qualitative descriptive. The result, there are 11 kinds of techniques. Among them are as follows: amplification, borrowing, literal translation, decription, particularization, modulation, transposition, linguistic compression, calque, generalization, reduction. In addition to changing the structure, the vocabulary of the packaging text also changes in meaning.